Indicadores microbiológicos de tratamento conjugado de lixiviado de aterro sanitário e esgoto sanitário em lagoas de estabilização rasas - Oliveira, Alinne Gurjão de (2013)
Treatment conjugate landfill leachate and sewage is widely used for reducing the concentration leachate pollutants. Stabilization ponds are the simplest processes, low cost and maintenance, used as alternatives for wastewater treatment. This study aimed to characterize the microbial community present in conjugate treatment in natura of landfill leachate and sewage in stabilization ponds. The experimental system was designed, and monitored at the Experiment Station Biological Sewage Treatment (EXTRABES) State University of Paraiba, Campina Grande - PB, Brazil (7 ° 13'11'' South, 35 ° 52 '31'' West and 550 m above sea level), consisting of four shallow stabilization ponds in series: a facultative pond, followed by three maturation ponds. A daily, the necessary volume of the substrate, from mixing 1% of landfill leachate, in natura, more 99% sewage, used for feeding the series of stabilization ponds. The average removal efficiency of thermotolerant coliforms and helminth eggs was 99.78% and 100%, respectively. The average concentration of the algal mass expressed as chlorophyll was 1032.6 ug / L. 29 taxa were identified phytoplankton included in six taxonomic classes: Cyanobacteria, 8 genres; Chlamydophyceae, 8 genres; Chlorophyceae, 9 genres; Euglenophyceae, 4 genres; Bacillariophyceae, 3 genres, and Zignemaphyceae, 1 gender.